Reversal of Warfarin-Associated Major Hemorrhage: Activated Prothrombin Complex Concentrate versus 4-Factor Prothrombin Complex Concentrate - Peksa, Gary D.; Mokszycki, Robert K.; Rech, Megan A.; Maynard, Brian; Panos, Nicholas G.; Sweis, Rolla T.; DeMott, Joshua M. (Thrombosis and Haemostasis, 2020)
Background Warfarin-associated major hemorrhage is frequently treated with prothrombin complex concentrates to correct international normalized ratio (INR).Objective This article aims to investigate the efficacy of activated prothrombin complex concentrate (aPCC) versus 4-factor prothrombin complex concentrate (4PCC) for vitamin K antagonist reversal in patients with warfarin-associated major hemorrhage.Materials and Methods This was a multicenter, retrospective cohort study. Patients included were age ≥ 18 years with pretreatment INR of > 1.5. Exclusion criteria were patients treated for urgent procedures without hemorrhage, treated but not taking warfarin, unavailable INR values, and pregnant patients. Patients were stratified into two groups: aPCC or 4PCC. The primary outcome was achievement of INR ≤ 1.5 at the posttreatment INR sampling. Secondary outcomes focused on thrombotic events and mortality.Results Of 342 patients, 237 patients received aPCC and 105 patients received 4PCC. After 1:1 propensity score matching, 86 patients remained in each group. In the matched cohort, the proportion of patients who achieved target INR ≤ 1.5 was greater with 4PCC (aPCC = 61 [70.9%] vs. 4PCC = 76 [88.4%]; 95% confidence interval [CI] –29.2% to –5.7%) and groups had comparable in-hospital thrombotic events and mortality. In the unmatched cohort, achievement of target INR ≤ 1.5 was greater with 4PCC (aPCC = 151 [63.7%] vs. 4PCC = 92 [87.6%]; 95% CI –32.7% to –15.1%).Conclusion In the treatment of warfarin-associated major hemorrhage, 4PCC compared with aPCC was associated with greater achievement of INR ≤ 1.5 with comparable thrombotic events and mortality. Further controlled studies are needed to confirm these findings and determine the optimal dosing strategy that maximizes efficacy and safety.
Keywords: anticoagulants; hemorrhage; prothrombin complex concentrates; warfarin; vitamin K antagonist